The Increasing of Students’ English Speaking by Using Community Language Learning (CLL) through Students English Association of LP3I (SEAL) at Politeknik LP3I Medan - Ramadani Ramadani; Andrysyah Andrysyah; Nurul Husnah Harahap; Rani Rakasiwi (Budapest International Research and Critics University, 2020)
This study dealt students’ English speaking by using Community Language Learning (CLL) through Students English Association of LP3I (SEAL). It used qualitative research design. It was conducted descriptively. This study aimed to know the increasing of students’ English speaking by using Community Language Learning (CLL) through Students English Association of LP3I (SEAL) at Politeknik LP3I Medan. The subjects were 55 students of Politeknik LP3I Medan. The use of instruments in this study was observation, interview and documentation. The theory of Koba, Ogawa & Wilkinson was used in this study. The data were analyzed by Miles, Huberman and Saldana analysis. The result of this study was Community Language Learning (CLL) had good result for students’ learning and can increase students’ English speaking at Politeknik LP3I Medan. This learning method was appropriate implemented to students of Politeknik LP3I Medan. Based on the data, all of response and result of this learning method got positive result and effect through the students of Politeknik LP3I Medan. This learning method can also upgrade students’ knowledge in speaking and got more vocabulary after implementing this activity. CLL can make the students happy and enjoy in studying English without forcing them to speak English. CLL can also make students brave and self-confidence to speak up in front of public.